Percutaneous Coronary Intervention in Left Main Coronary Artery Disease - A Case Report - Chowdhury, AHK; Uddin, M Saleh; Khalequzzaman, Md; Islam, AKM Monwarul; Ali, Shawkat; Roy, Udoy Shankar; Quayyum, Md Abdul; Shikder, Mamunur Rashid; Gani, Mohammad Nasimul; Zaman, Shahana; Rahman, Mahbubur; Islam, SK Ziarat (University Heart Journal, 2012)
Not available DOI: http://dx.doi.org/10.3329/uhj.v8i1.11669 University Heart Journal Vol. 8, No. 1, January 2012